Potensi Inhibisi Enzim α-Glukosidase Dari Ekstrak Kulit Buah Labu Air (Lagenaria siceraria) Sebagai Antidiabetes - Harry Noviardi; Freddy Arifta Nassel; Moh. Syarif (Fakultas Farmasi Universitas Setia Budi, 2020)
Diabetes mellitus is a metabolic disorder characterized by hyperglycemia associated with metabolic abnormalities of carbohydrates, fats, and proteins caused by decreased insulin secretion or decreased insulin sensitivity or both and causes chronic complications. Bottle gourd (Lagenaria siceraria) contains antioxidant compounds such as flavonoids, phenols, and tannins which are used to reduce glucose levels in the blood. The research aimed to determine the potential activity of water and ethanol extracts with a concentration of 70%, and 96% of bottle gourd skin in inhibiting the activity of the α-glucosidase enzyme. Bottle gourds were extracted with water and ethanol using the maceration method. The extracts were identified by its chemical compound and tested for the inhibitory activity of the α-glucosidase enzyme.Based on phytochemical results, bottle gourd skin extracts contained flavonoids and saponins. Bottle gourd water extract had the lowest inhibitory.The highest value was ethanol 96% extract. Based on the results of the one-way ANOVA analysis test there was a significant difference in the inhibition of the enzyme α-glucosidase and based on the Duncan Test Pos Hoct Test the four treatments were significantly different. The best IC50 value in ethanol 96% bottle gourd skin extract was 0.487%. Therefore, ethanol 96% bottle gourd skin extract had the potential to inhibit α-glucosidase.